2021
DOI: 10.1021/acsami.1c06038
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dense and Stable p-Type Thin-Film Transistor Based on Atomic Layer Deposition SnO Fabricated by Two-Step Crystallization

Abstract: Over the past several decades, tin monoxide (SnO) has been studied extensively as a p-type thin film transistor (TFT). However, its TFT performance is still insufficient for practical use. Many studies suggested that the instability of the valence state of Sn (Sn2+/Sn4+) is a critical reason for the poor performance such as limited mobility and low on/off ratio. For SnO, the Sn 5s–O 2p hybridized state is a key component for obtaining p-type conduction. Thus, a strategy for stabilizing the SnO phase is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 46 publications
2
23
0
3
Order By: Relevance
“…As a result, it has been challenging to develop high-performance p-type metal oxide semiconductors. Nevertheless, with the great research efforts, the charge transport characteristics of p-type metal oxide semiconductors such as copper (II) oxide (CuO) [ 85 , 86 ], and tin (II) oxide (SnO) [ 87 , 88 ] have been improved, which expands their applicability into metal oxide semiconductor-based complementary inverters and logic circuits.…”
Section: Vertically Integrated Electronic Devices Based On Emerging S...mentioning
confidence: 99%
“…As a result, it has been challenging to develop high-performance p-type metal oxide semiconductors. Nevertheless, with the great research efforts, the charge transport characteristics of p-type metal oxide semiconductors such as copper (II) oxide (CuO) [ 85 , 86 ], and tin (II) oxide (SnO) [ 87 , 88 ] have been improved, which expands their applicability into metal oxide semiconductor-based complementary inverters and logic circuits.…”
Section: Vertically Integrated Electronic Devices Based On Emerging S...mentioning
confidence: 99%
“…The excellent device integrity was closely related to the process temperature, and the field-effect mobility, on/off ratio, and subthreshold swing ( SS ) values obtained in this study are the best-reported data for top-gate p-TFT devices. In the same year, Kim et al obtained SnO films with a density of 6.4 g/cm and high Hall mobility close to 5 cm 2 ·V −1 ·s −1 by growing highly c-axis-oriented SnO in the initial stage [ 69 ], followed by further crystallization along the in-plane direction via a post-annealing process. The prepared SnO-TFT had a field-effect mobility of up to 6.0 cm 2 ·V −1 ·s −1 , which is a rather high value compared to the long-term stability of SnO-TFTs reported thus far.…”
Section: P-type Sno Tftsmentioning
confidence: 99%
“…The development of oxide semiconductors has attracted significant interest due to their compatibility with low-temperature processes to support many emerging applications, including transparent and flexible displays and transparent complementary metal-oxide semiconductor (CMOS) circuits. , For instance, transparent amorphous InGaZnO with mobility greater than 10 cm 2 V –1 s –1 has been successfully fabricated at room temperature and has proven to be useful in driving thin-film transistors in flat panels and flexible displays. , Unfortunately, p-type oxide semiconductors with mobility comparable to n-type semiconductors are difficult to achieve because the valence band (VB) as a hole conduction pathway in these materials inherently consists of highly localized and anisotropic O 2p orbitals . It is their poor p-type properties that hinder the application of oxide semiconductors in low-power and high-performance transparent CMOS logic circuits, where a balanced performance across the p- and n-type devices is essential. , Recently, several oxide materials have been proposed to produce high-performance transparent p-type semiconductors, including copper-based ternary oxides (CuMO 2 , M = Al, Ga, In, etc. ), spinel oxides (ZnM 2 O 4 , M = Rh, Co, Ir, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the feasibility of p-type conductivity in SnO has been experimentally demonstrated using several techniques, including reactive magnetron sputtering, ,, atomic layer deposition, , pulsed laser deposition, ,, e-beam evaporation, ,, and solution process. , However, the performance of the prepared SnO still varies greatly depending on the type of sample and the resulting crystal structure. For bulk SnO polycrystals, a hole mobility as high as 30.0 cm 2 V –1 s –1 has been reported .…”
Section: Introductionmentioning
confidence: 99%